PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPENUMBER HEADS TOGETHER (NHT) UNTUK MENINGKATKAN KREATIVITAS DAN PRESTASI BELAJAR - Riniati (UNIB Press, 2022)
This study aims to describe the application of the number heads together (NHT) cooperative learning model and to describe the effectiveness of the number heads together (NHT) type of cooperative learning to increase the creativity and learning achievement of Indonesian class XI students of SMA Negeri 1 Kikim Timur Lahat. The research method used was Classroom Action Research (PTK) and quasi-experimental. The research subjects were students of class XI IPS 3 semester Two of the 2020/2021 academic year of SMA Negeri 1 Kikim Timur Lahat. The quasi-experimental sample was class XI IPS 2 and class XI IPS 1. The number of students for the PTK class was 31 students, for the Experiment class there were 30 students, and for the control class there were 30 students. The data collection method in this study used an observation sheet for the implementation of the Cooperative Learning Model Type number heads together (NHT), an observation sheet for increasing creativity, and a test of learning outcomes. The data analysis used tests which consisted of different tests between cycles and different tests of two unrelated samples. The results showed that the application of the number heads together (NHT) cooperative learning model could increase the creativity and learning achievement of Indonesian class XI students of SMA Negeri 1 Kikim Timur Lahat and effectively improve student learning outcomes in Indonesian subjects.